9-3(x+2)=

Simple and best practice solution for 9-3(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3(x+2)= equation:


Simplifying
9 + -3(x + 2) = 0

Reorder the terms:
9 + -3(2 + x) = 0
9 + (2 * -3 + x * -3) = 0
9 + (-6 + -3x) = 0

Combine like terms: 9 + -6 = 3
3 + -3x = 0

Solving
3 + -3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -3x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = 0 + -3
-3x = 0 + -3

Combine like terms: 0 + -3 = -3
-3x = -3

Divide each side by '-3'.
x = 1

Simplifying
x = 1

See similar equations:

| 6x-8=16+4x | | -21x^2-33x+18= | | 270+16x=14x | | y+16=12 | | 4w^2-8wx-21x^2= | | 0.5cos(x)+0.08cos(2x-0.1)=0 | | 13x^2-27+28=0 | | 3m+23=8m-2 | | 4(w+1)+w=5(-1)+9 | | (h*f)(1)=4x-1-x+4 | | a^3y+1=0 | | x-2=7x+50 | | 8r+3=5r+12 | | -3(2x+4)=0 | | x=6-0.5y | | 7(11-8)=21 | | 7(p-8)=21 | | -7x=-49+98 | | 2x+2(2)=-10 | | 45+x=602 | | (3r-2s)(3r-2s)= | | 116-w=294 | | -8x-2(-1.5)=-13 | | -8(2)-2y=-13 | | 4a+(10-4a)=10 | | 5p-9=29+12 | | 500.00+.35=2.50x | | 9.8=6x+8.6 | | -0.09x=-2.7 | | y-7.1=3 | | 500.00+35x=2.50x | | 6.1x+9-2.1x=1 |

Equations solver categories